Michael Ryan's Writings on Medical Ethics - Brody, Howard.; Meghani, Zahra.; Greenwald, Kimberley. (Philosophy and Medicine, 2010)
Michael Ryan (d. 1840) remains one of the most mysterious figures in the history of medical ethics, despite the fact that he was the only British physician during the middle years of the 19th century to write about ethics in a systematic way. Michael Ryans Writings on Medical Ethics offers both an annotated reprint of his key ethical writings, and an extensive introductory essay that fills in many previously unknown details of Ryans life, analyzes the significance of his ethical works, and places him within the historical trajectory of the field of medical ethics. Gathers the key ethical writings of an often overlooked author in one volume Provides first detailed biography of Ryan Ryan is compared and contrasted in detail with predecessors, Gregory and Percival Highlights the unique, original contributions of Ryan to medical ethics